Intercultural competence: A phenomenological study of students’ intercultural experience in Universiti Utara Malaysia - Syarizan, Dalib (2014)
Studies in the field of intercultural competence are expanding. Although numerous studies have been done, there are two important issues that need to be considered. First, current studies are dominated by the Western perspective that places a focus on the individual in evaluating intercultural competence. Second, intercultural competence is often analyzed by looking at a national culture that is treated as homogenous. This tendency falls short to illuminate ethnic diversities within a nation and it is inadequate in capturing the intercultural experiences in the non-Western context. Accordingly, this study is conducted to re-examine an intercultural competence model developed by Deardorff in 2004 by exploring the nature of students’ intercultural experience in Universiti Utara Malaysia and the conception of intercultural competence in the light of their experience. This study utilized a phenomenological method. In-depth interviews and focus groups involving ethnically diverse students were used as methods of data collection. Snowballing sampling was implemented in this study. Data were analyzed using techniques advocated by Moustakas in 1994. The findings of this study indicate that, first; students’ intercultural experience comprises two core themes which include identifying self as an ethnic being and encountering differences between self and the Other. Second, the conception of intercultural competence encompasses three core themes which include cultural understanding, respect, and language ability. The findings differ from that of Deardorff’s model since the identified core themes emphasize on relationship building rather than the individual in analyzing intercultural competence. This study also shows a new perspective on intercultural competence that highlights the salience of ethnic identities in the students’ intercultural experience as an important element in developing intercultural competence. Thus, Deardorff’s model is extended by including a focus on relationship building and intercultural experience that illuminates diverse ethnic identities in explaining intercultural competence. This study contributes into a reconceptualization of intercultural competence from the Western perspective and explains a new perspective with a focus on relationship building as well as intercultural experience